PELAKSANAAN PELAYANAN PEMERINTAH DESA TERHADAP MASYARAKAT DI DESA RANTAU PANJANG KECAMATAN SEBAWI KABUPATEN SAMBAS - Hasiah, Hasiah; Tamrin, Tamrin; Somiadi, Somiadi (Universitas Merdeka Madiun, 2021)
This study aims to analyze the duties and authorities of the village government which is the leading government organization in the delivery of public services. Village government public services must be based on the minimum service standards as stated in the Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 2 of 2017 concerning Village Minimum Service Standards that the Village Government must bring services closer to the community, facilitate services to the community, open service to the community and the effectiveness of services to the community. Public. This study uses a qualitative field research method with an empirical juridical approach. The results of the study concluded that there are still deficiencies in the implementation of the duties and authority of the village government in serving the community in Rantau Panjang. This is indicated by the fact that there are still people who do not have population data, there are concurrent positions in the Kasi and Kaur departments, and still not implemented regarding village determination regarding the village minimum service standard